Avaliação da ação conjunta parede-viga considerando efeito arco - Borsato, José Antonio Teodoro (2018)
This work presents the behavior of a structural masonry wall over a reinforced concrete beam, considering the influence of beam and wall stiffness, as well as the beam restraints and the presence of openings in the wall, investigating the occurrence and intensity of the arch effect. Several computational models were made and, after obtaining the results, they are compared to attest the influence in the behavior. It was concluded that the Davies & Ahmed method is more adequate, increasing the stiffness of the wall relative to the beam intensifies the arc effect, and decreasing the relation has the opposite effect, the existence of the third support and openings generate new distributions of tensions.